Research and Application on a Novel Clustering Algorithm of Quantum Optimization in Server Load Balancing. (6th April 2014) - Yumin, Dong; Shufen, Xiao; Fanghua, Jia; Jinhai, Li
Abstract : A quantum optimization scheme in network cluster server task scheduling is proposed. We explore and research the distribution theory of energy field in quantum mechanics; specially, we apply it to data clustering. We compare the quantum optimization method with genetic algorithm (GA), ant colony optimization (ACO), simulated annealing algorithm (SAA). At the same time, we prove its validity and rationality by analog simulation and experiment.